The behavior of migraine in patients with Parkinson's disease - Celmir de Oliveira Vilaça; Marco Antonio Araujo Leite; Jano Alves de Souza; Marco Orsini; João Santos Pereira; Clayton Amaral (MDPI AG, 2015)
Parkinson's disease (PD) is characterized by the degeneration of dopaminergic systems in the central nervous system. In migraine it is supposed to occur hyperactivation of central dopaminergic pathways. We verified the hypothesis of improved migraine in patients who manifest PD. We evaluated 109 patients with PD over 40 years (57 men and 52 women) about the presence throughout the life of migraine, as well as the possibility of improvement in migraine after the onset of motor symptoms of PD. This group was compared to a control group of 152 people (41 men and 152 women) without PD regarding the presence of migraine and its improvement. Twenty-one patients manifested migraine in the group with PD (16 women and 5 men) in which 13 reported improvement in migraine after the onset of symptoms of PD. Among the controls, 37 interviewed had migraine history (32 women and 5 men) among which 20 showed improvement. There was no significant difference when comparing the two groups (χ21:0,05=0.337; P<0.382). We were unable to relate the improvement of migraine with the emergence of PD motor signs, despite the degeneration of dopaminergic pathways of the central nervous system.